Abdominoplasty for Ladd's procedure: optimizing access and esthetics. Issue 4 (October 2017) - Aliotta, Rachel; Kundu, Neilendu; Stallion, Anthony; Cavaliere, Christi
Abstract : Rotational anomalies occur when there is an abnormal arrest of rotation in the embryonic gut during development. The characteristic population affected is considered to be infants or young children, but in clinical practice, can be found in older children and adults as well. In these patients, the Ladd procedure is performed, whereby the abdomen is opened using traditional incisions, such as the midline laparotomy, for full visualization of the abdominal cavity. Despite providing excellent visualization, approaches such as this carry both increased surgical-site morbidity and an often-displeasing incision and visible scar. In this case report, we advocate consideration of the low transverse pfannenstiel incision and approach used traditionally in cosmetic and reconstructive abdominoplasty for surgical access to the abdomen for Ladd's procedure. We believe that this alternative approach provides superior visualization without compromising the integrity or the esthetics of the abdominal wall in appropriate populations desiring to minimize the morbidity and visibility of their scar.